Implementation of ultrasound-guided cannulation training for foundation doctors - Mia Pham; Robert Aldous; Stephan Brincat (Clinical Medicine)
Peripheral intravenous cannulation (PIVC) is an essential skill for newly qualified foundation doctors. It has high failure rates, resulting in care delays, pain and infection. We explored the perceived impact of ultrasound-guided PIVC (US-PIVC) training on confidence when performing difficult-access PIVC. We surveyed 88 foundation doctors to evaluate their perceptions of US-PIVC. Each cohort of participants was given two sessions over a 2-month period. Confidence was assessed using electronic questionnaires through 5-point Likert scales and free text responses. Confidence when performing PIVC with difficult access, regardless of US, increased significantly following the course (p < 0.01). This was also true regarding confidence when performing US-PIVC (p < 0.01.). Key themes identified included technical skills, confidence and clinical utility.